The complete mitochondrial genome of Mystus gulio Hamilton (Siluriformes: Bagridae) and its phylogenetic implication - Hoang Danh Nguyen; Minh Thiet Vu; Hoang Dang Khoa Do (Mitochondrial DNA. Part B. Resources, 2023)
Mystus gulio Hamilton, also called long whiskers catfish, is an endemic fish and a common food in some Asian countries. In this study, the complete mitochondrial genome of M. gulio was sequenced using the MinION system (Oxford Nanopore Technologies). The mitochondrial genome is 16,518 bp in length (41.1% [G + C] content) and consists of 13 protein-coding genes, 22 transfer RNA genes, and two ribosomal RNA genes. The results of phylogenetic analysis inferred from whole mitochondrial genomes of Mystus and related species in the family Bagridae revealed that M. gulio is closely related to Mystus cavasius.